Impact of Workload and Work-Life Balance on Aviation Safety at Soekarno-Hatta ATC - Giga Valtian Zepa; Hari Kurniawanto; Dimas Hari Cahyo; Daniel Dewantoro Rumani (Research Synergy Press, 2025)
The increasing complexity of air traffic operations and the high cognitive demands placed on Air Traffic Controllers (ATCs) underscore the critical need to address factors affecting performance and safety. This study investigates the influence of workload and work-life balance (WLB) on safety outcomes among ATCs at Soekarno-Hatta International Airport through a Systematic Literature Review (SLR). This research is motivated by the growing concern over fatigue-related incidents in aviation, particularly in high-density airspace environments. By synthesizing empirical and theoretical findings from peer-reviewed literature, this study explores how excessive workload, rigid shift structures, and insufficient recovery periods contribute to cognitive fatigue, diminished attentional control, and elevated error rates. In contrast, structured WLB interventions—such as optimized shift rotations, mandatory rest periods, and supportive scheduling policies—are found to mitigate fatigue and enhance operational vigilance. However, the applicability of flexible working hours in ATC settings is constrained by the operational and regulatory frameworks of the aviation industry, particularly the standards set by the International Civil Aviation Organization (ICAO). This study contributes to the discourse on aviation human factors by advocating tailored fatigue risk management strategies and institutional support mechanisms to improve ATC well-being and ensure sustained aviation safety performance